Simulation and optimization of an α-type Stirling engine for high-temperature latent heat storage applications - Mohammad A.S. Khasawneh; Mohamed Elsir; Sherif A. Yehya; Asem Alemam (Energy Conversion and Management: X)
As the transition to renewable energy grows, reliable dispatchable energy storage systems are crucial for grid stability. This study investigates the performance of an α-type Stirling engine integrated with high-temperature latent thermal energy storage (TES), which offers high energy density and constant-temperature charging and discharging. The effects of key operating parameters, including charging pressure, temperature differences, and shaft speed, are analyzed using hydrogen as the working fluid. Results show that output power and efficiency follow similar trends with changes in hot and cold side temperatures but exhibit opposite behaviors with engine speed and pressure variations. Single-objective optimization achieved a maximum power output of 15.2 kW with 46.9 % efficiency. A multi-objective optimization framework was employed to construct the Pareto frontier, offering a comprehensive view of performance trade-offs. Among the many non-dominated solutions, 15.23 kW at 44 % efficiency was observed. This approach empowers decision-makers with the flexibility to select configurations based on specific operational goals, such as maximizing output or minimizing energy losses. Sensitivity analysis identifies shaft speed and pressure as the most influential factors on power output. These findings validate the engine’s integration with TES systems and highlight opportunities for further optimization to enhance its performance and support sustainable energy storage solutions.